Magnetic Airless Tyre (MAT) - Sivarao, Subramonian (2012)
The present invention relates to a magnetic airless tyre comprising: a rim having hub mounting plate and rim core; a suspension cylinder; characterised in that a magnet secured to the wall of the suspension cylinder with fastener; a loading shaft having: grooved rib as a guide for vertical strokes guided by guiding pin secured on the wall of the suspension cylinder; a retention cap secured to hand hole; a loader pad is fixed to loader shaft with connecting pin; a terminal plate holder attached at the back side of the first rim having: negative terminal and positive terminal; a skin is attached to the rim to provide canvas and cushion for loader pad acting as tyre which directly contacts the ground.